Credence goods, costly diagnosis, and subjective evaluation - Helmut Bester; Matthias Dahm (Sonderforschungsbereich/Transregio 15 - Governance and the Efficiency of Economic Systems (GESY), 2014)
We study contracting between a consumer and an expert. The expert can invest in diagnosis to obtain a noisy signal about whether a low-cost service is sufficient or whether a high-cost treatment is required to solve the consumer's problem. This involves moral hazard because diagnosis effort and signals are not observable. Treatments are contractible, but success or failure of the low-cost treatment is observed only by the consumer. Payments can therefore not depend on the objective outcome but only the consumer's report, or subjective evaluation. A failure of the low-cost treatment delays the solution of the consumer's problem by the high-cost treatment to a second period. We show that the first-best solution can always be implemented if the parties' discount rate is zero; an increase in the discount rate reduces the range of parameter combinations for which the first-best can be obtained. In an extension we show that the first-best is also always implementable if diagnosis and treatment can be separated by contracting with two different agents.
urn:nbn:de:bvb:19-epub-21900-7
Keywords: D82; D83; D86; I11; 330; credence goods; information acquisition; moral hazard; subjective evaluation